Extra-axial isolated cerebral varix misdiagnosed as convexity meningioma: A case report and review of literatures. Issue 26 (June 2016) - Tan, Zhi-Gang; Zhou, Qian; Cui, Yan; Yi, Lei; Ouyang, Yian; Jiang, Yugang
Abstract : Abstract: Isolated cerebral varix is a rare cerebrovascular anomaly, which is easily misdiagnosed as other brain tumors. A 59-year-old female patient with noncontributory medical history presented with headache and insomnia for the last 2 months. Upon admission, her neurological examination was unremarkable. Magnetic resonance imaging revealed a well-demarcated extra medullary mass, 11 × 11 mm in size, within the subdural space at the right frontal lobe. The lesion was initially interpreted as a convexity meningioma. After conducting a craniotomy on the patient, an extra-axial varix was exposed and resected subsequently. The patient's headache was resolved soon after surgery and charged without neurologic sequelae. Extra-axial isolated cerebral varix is mimicking convexity meningioma on MR images and should be considered as a differential diagnosis. The focal erosion in the inner table of the skull could be an important character of extra-axial isolated cerebral varix. An extremely round shape and smooth contour of the lesion was another important character. Isolated cerebral varix is rare vascular lesion that is treated surgically in the case of rupture or compression of adjacent structures. The information obtained with noninvasive imaging techniques should include CTA to make a clinical decision.